Basics of CMOS cell design - Sicard, Etienne; Bendhia, Sonia Delmas (McGraw-Hill's AccessEngineering., 2007)
This book is suitable for electronic circuit designers and electronic engineering students. It includes a CD-ROM which contains circuit simulation tools that can be used to work the many examples presented in the text. It covers MOS devices and technology, MOS modeling, the inverter, basic gates, analog cells, and more.